GEORADAR INVESTIGATION AT THE KEDULAN TEMPLE EXCAVATION SITE, KALASAN, YOGYAKARTA - Salahuddin Husein; Saptono Budi Samodra; Subagyo Pramumijoyo; Wahyu Astuti (Journal of Applied Geology, 2015)
Kedulan Site is the buried and ruined 9th century Mataram Hindu Kingdom temple, located in Tirtomartani Village, Kalasan District, Sleman Regency, Yogyakarta Special Province. This temple was incidentally discovered by sand diggers on 24 November 1993 under several meter thick of fluvio-volcanic deposit of the modern Merapi. Several technical studies were needed to carefully excavate the temple, including geology and geophysical approaches. One of the geophysical method have been applied was ground penetration radar (georadar). This method uses radar technology to obtain a continuous profile of the shallow sub-surface and thus allows scientists to image soil substratums based on differing dielectric constants. Georadar investigation by Department of Geological Engineering, Faculty of Engineering, Universitas Gadjah Mada, was conducted on 4 December 2007. The main purpose was to identify the location of the outer stone fence as an estimation to define the temple site area to be excavated. About one line was chosen to cross the site in north-south direction in a distance of 328 m. Two runs were completed on the same line but different courses, i.e. forward and backward, where one was checked with another. The result indicates the presence of the outer stone fence was possibly buried in a depth of 7 m. It was located about 40 m distance outside the inner stone fence. Assuming the fences were quadrangle relative to the main temple, hence it is estimated that the site area to be excavated is about 13.830 m² and total 96.808 m³ gravels and sands to be removed.